Pengaruh Praktek Lapangan Kependidikan terhadap Minat Menjadi Guru pada Mahasiswa Program Studi Pendidikan Agama Islam Universitas Negeri Padang - Nopel, Nopel; Afroo, Fakhriyah Annisa (YASIN, 2025)
The limited number of studies examining the impact of Praktek Lapangan Kependidikan (PLK, or Educational Field Practice) on the interest in becoming a teacher—particularly among students of the Islamic Religious Education (PAI) study program—serves as the background for this research. Direct experience during PLK is believed to play a significant role in shaping students’ perceptions, motivation, and readiness to pursue teaching as a profession. This study aims to analyze the influence of PLK on the interest in becoming a teacher among 2021 cohort PAI students at Universitas Negeri Padang. A quantitative approach with a correlational research design was employed. A sample of 56 students was selected using purposive sampling. Data were collected through PLK grade documentation and a questionnaire on teaching interest, and then analyzed using simple linear regression with IBM SPSS Statistics 22. The results indicate that the average PLK score was 87.21 (moderate category), and the average interest in becoming a teacher was 91.46 (moderate category). The product-moment correlation test yielded an r value of 0.901 with a significance level of 0.000 < 0.05, indicating a very strong and statistically significant relationship between PLK and interest in becoming a teacher. The coefficient of determination (R²) was 0.811, suggesting that 81% of the variance in teaching interest is explained by PLK. These findings confirm that positive experiences during PLK—such as support from mentor teachers and successful teaching practices—significantly contribute to increasing students' interest in becoming teachers. This study reinforces experiential learning theory and offers practical recommendations for higher education institutions to enhance PLK implementation through systematic mentoring, evaluation, and reflection.